Pemberdayaan Kolaboratif dengan WCC Dian Mutiara dan Aktivasi Forum Dharma Wanita Sahabat Kampus dalam Mencegah Kekerasan di Universitas Brawijaya - Wahyuni, Lilik; Sukesi, Keppi; Minarti, Sri; Wijayanti, Jamila (Jurnal Gramaswara: Jurnal Pengabdian kepada Masyarakat, 2024)
The aim of this community service activity is to collaborate with WCC DMP to increase the role of the Campus Friends Dharma Wanita Forum as paralegal volunteers, develop empowerment strategies, and provide technical guidance for victims in efforts to prevent various forms of violence on campus. This activity is useful for providing education to the public regarding PPKS so that awareness is formed. Apart from that, students can submit complaints and report to the DWP who have received training regarding PPKS. As for lecturers, the effort to involve DWP in PPKS is a positive synergy between lecturers and partners for PPKS, and partners as practitioners will receive a lot of reinforcement regarding PPKS. The activity design consists of coordinating the service team, preliminary survey (informal approach), activity permit process (formal), location identification, brainstorming, FGD, increasing human resource capacity, and activity reporting. The service achievements that have been obtained are in the form of holding ToT training activities for Dharma WanitaSatu volunteers and providing assistance in the Prevention and Handling of Sexual Violence (PPKS). The service activity was successfully held involving Dharma Wanita PBB, Directorate General of Research and Technology, Association of Indonesian Women/Gender and Children Study Centers (ASWGI), Dharma Wanita PBB, Universitas Brawijaya PPKS Task Force, Center for Gender Studies, and WCC Dian Mutiara. Apart from ToT, the Center for Gender Studies and Dharma Wanita Friends of the Campus also carries out outreach in faculties to convey to new students about the Dharma Wanita Friends of the Campus program.   Keywords: empowerment; prevention; gender-based violence; WCC-DWP-PSG collaboration